GLOBECOM '03. IEEE Global Telecommunications Conference (IEEE Cat. No.03CH37489)
DOI: 10.1109/glocom.2003.1258798
|View full text |Cite
|
Sign up to set email alerts
|

Server and route selection method for QoS-based anycast protocol

Abstract: The anycast communication protocol is to select the best server and the best route for a particular client from a group of replicated servers with the same contents. As users have come to demand contents with high QoS, the necessity to support the anycast communications in QoS networks has grown. In this paper, we propose a server and route selection method with application-level QoS-based anycast protocol. The protocol we propose has the following advantages. 1) The latest server and route information can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
1

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(29 citation statements)
references
References 6 publications
1
27
1
Order By: Relevance
“…Regarding the work by Nakaniwa et al [9], the first two problems are the same as those found in the work by Hao et al [8] and mentioned above. In addition, the protocol broadcasts a search message to all candidate servers in order to find the best server.…”
Section: Discussion Of the Existing Protocolssupporting
confidence: 55%
See 4 more Smart Citations
“…Regarding the work by Nakaniwa et al [9], the first two problems are the same as those found in the work by Hao et al [8] and mentioned above. In addition, the protocol broadcasts a search message to all candidate servers in order to find the best server.…”
Section: Discussion Of the Existing Protocolssupporting
confidence: 55%
“…Since Lin et al [10] balanced only the server loading and network traffic, Figs. 9-11 compare and evaluate four different approaches, namely those proposed by Hao et al [8], Nakaniwa et al [9], Lin et al [10] and the proposed protocol. The remaining figures compare and evaluate only three different approaches, namely those proposed by Hao et al [8], Nakaniwa et al [9] and the proposed protocol.…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations